Penerapan Aksiologi Filsafat Islam dalam Pembentukan Karakter Anak Usia Dini di RA Bustanul Qur’an - Mujib, Ahmad; Mujiburrohman, Mujiburrohman (Lembaga Yasin AlSys, 2025)
This study aims to explain the application of axiological values in Islamic philosophy to the process of character building in early childhood education at RA Bustanul Qur’an. Axiology, as a branch of philosophy that examines values and ethics, plays a crucial role in establishing the foundation of character from an early age, particularly within Islamic education. Using a qualitative descriptive approach, the study explores the integration of Islamic values such as honesty, mutual assistance, discipline, and compassion into learning activities at the RA. The findings indicate that the consistent application of Islamic axiological values can shape children into religious, independent individuals with a high degree of social sensitivity. The study also emphasizes the importance of collaboration between teachers and parents in optimizing character formation through the instillation of Islamic values from an early age.